PENGARUH LATAR BELAKANG PENDIDIKAN DAN LATAR BELAKANG POLITIK TERHADAP PENGAWASAN KEUANGAN DAN BARANG MILIK DAERAH OLEH DEWAN PERWAKILAN RAKYAT DAERAH DENGAN PARTISIPASI MASYARAKAT SEBAGAI VARIABEL PEMODERASI - Deisyi, Yulita; Asnawi, Meinarni; Simanjuntak, Aaron M. A. (Fakultas Ekonomi, Universitas Cenderawasih, 2019)
This study aims to determine the effect of personal background, political background, andcommunity participation as a moderating variable on the supervision of financial management andregional assets. This research was conducted in Pegunungan Bintang Regency using a sample of 31respondents. Sampling method with a saturated sampling method. The data analysis technique usedis the instrument test technique including moderation regression and multiple linear regression. Theresults show partially that the variable background of education, political background, andcommunity participation did not significantly influence the supervision of financial managementand regional assets.